Participatory technology development in Upper Karkheh River basin, Iran - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The Participatory Technology Development (PTD) project, a component of PN24 ‘Livelihood Resilience in Dry Areas’ which is a project of the CGIAR Challenge Program on Water and Food, was extensively documented in the book, “Gathering Wisdom from the Field: Participatory Technology Development in Upper Karkheh River Basin, Iran.” The book outlines how the research paradigm in Iran transformed from the conventional one towards participatory and people-centered research.